0090 Learning and Memory in Short and Long Sleeping Inbred Drosophila Melanogaster Lines. (27th April 2018) - Smith, K R; Harbison, S T
Abstract: Introduction: While the overall function of sleep is largely unknown, many hypothesize that sleep plays an integral part in learning and memory. Previously, we generated populations of long- and short-sleeping flies via an artificial selection scheme. We inbred lines of flies from these populations that have stable long and short sleep duration phenotypes. Here we propose to investigate whether the extreme long or short sleep in these flies is correlated with changes in learning and memory. Methods: We utilized an aversive phototaxis suppression assay to test learning and memory ability in the Sleep Inbred Panel, a collection of 39 wild-derived extreme short- and long-sleeping inbred lines. This assay exploits the natural phototactic behavior in flies by training them to avoid a lighted chamber with an aversive stimulus. Flies are trained with three training sessions of four trials each. A fourth session measures the fly's ability to correctly choose the unlighted chamber in four trials, with a perfect score being 4.0. Each fly was tested to ensure that it had normal phototactic behavior prior to training. In a pilot study, we trained and tested males and females from four lines: a long-sleeping line (SIP_L1_9), two short-sleeping lines (SIP_S1_9 and SIP_S2_7), and a wildtype control line with moderate sleep (DGRP_373). Results: The long sleeper line SIP_L1_9 had a mean score of 0.7, while the short sleeper lines SIP_S1_9 and SIP_S2_7 had scores of 1.2 and 1.6, respectively. All three lines had lower scores than the control score of 2.5, and the scores of lines SIP_L1_9 and SIP_S1_9 were statistically significant ( P ≤ 0.05). Conclusion: Our preliminary data suggests that both short-sleeping and long-sleeping flies may have learning and memory deficits. We will present the results of these tests as well as the scores of the remaining lines. Support (If Any): This work was supported by the Intramural Research Program of the National Institutes of Health, The National Heart, Lung and Blood Institute.